2015
DOI: 10.1007/s12031-015-0570-1
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2

Abstract: Our previous study has showed that co-grafted Schwann cells (SCs) promote proliferation and migration of the grafted oligodendrocyte precursor cells (OPCs). However, how the co-grafted SCs affect OPCs has not been clarified. In the present study, we confirmed that SC-induced proliferation and migration of OPCs were mediated by SC-secreted factors using SC-conditioned medium (SCM). Then, we detected several candidate factors, PDGF-AA, FGF-2, and IGF-1, in SCs and SCM, and their receptors in OPCs. Finally, by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Our previous study showed that co-transplantation of SCs and OPCs promoted the survival, proliferation and migration of transplanted OPCs in vivo and improved neurological recovery following SCI (Hu et al, 2013). A subsequent in vitro study confirmed that SCs modulated the proliferation and migration of OPCs by secreting platelet-derived growth factor (PDGF)-AA and fibroblast growth factor-2 (FGF)-2 (Chen et al, 2015); moreover, we showed that PDGF-AA stimulated the proliferation of OPCs and their differentiation into OLs at later stages (Hu et al, 2008). We therefore speculated that PDGF-AA administration would have similar effects as SCs in OPC transplantation for SCI repair.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Our previous study showed that co-transplantation of SCs and OPCs promoted the survival, proliferation and migration of transplanted OPCs in vivo and improved neurological recovery following SCI (Hu et al, 2013). A subsequent in vitro study confirmed that SCs modulated the proliferation and migration of OPCs by secreting platelet-derived growth factor (PDGF)-AA and fibroblast growth factor-2 (FGF)-2 (Chen et al, 2015); moreover, we showed that PDGF-AA stimulated the proliferation of OPCs and their differentiation into OLs at later stages (Hu et al, 2008). We therefore speculated that PDGF-AA administration would have similar effects as SCs in OPC transplantation for SCI repair.…”
Section: Introductionsupporting
confidence: 58%
“…As previously mentioned, SCs promote OPC proliferation and migration through secreting PDGF-AA and FGF-2 (Chen et al, 2015). In the present study, we only explored the effect of PDGF-AA-overexpressing OPCs on SCI.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For instance, transient exposure to FGF-2 has no effect on OPC migration, whereas OPCs show long-term migration when exposed to PDGF-A under the same conditions [26]. Treating cells with both growth factors leads to faster migration compared to either alone, and also converts progenitors from slowly to rapidly dividing cells [26,[35][36][37][38]. Similar to PDGF-A, FGF-2 promotes OPC migration via the ERK1/2 signaling pathway after binding to its receptors FGFR1, which is necessary for FGF-2-induced migration [27,37,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Schwann cells (SCs) are peripheral nervous system-derived myelin-forming cells that produce growth-promoting factors and cell adhesion molecules (Acheson et al, 1991;Chiu et al, 1991;Oudega and Xu, 2006). Our previous study showed that SCs induce proliferation and migration of OPCs via secretion of platelet-derived growth factor (PDGF)-AA and fibroblast growth factor (FGF)-2 in vitro (Chen et al, 2015); moreover, co-transplantation of SCs and OPCs promoted survival, proliferation and migration of transplanted OPCs in vivo and improved neurological recovery following SCI (Hu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%